Lawyers as membersof a criminal organization. Notes on the neutral conduct in the practice ofthe profession of lawyer and professional secrecy - Delgado Castro, César Antonio (2019)
Routine criminal forensic practice in our country is usually based on the abusive practice of the right to exercise law and of the right to professional secrecy and whose criminal conduct that violates the criminal law or that transgresses the Code of Ethics of the Lawyer is justified with the worn-out argument of the neutral or social adequate conduct. However, this is often because the lawyer does not wish to become eventually involved in the facts under investigation or wishes to protect the investigated party who he sponsors – or sponsored – rather than for reasons directly related to professional secrecy or to the proper practice of the profession, hence our legal authorities and operators must pay close attention to prevent the poor use of the profession and of the right to professional secrecy. There are no neutral behaviors per se because anyone who can generically and abstractly be qualified as neutral, that is, criminally irrelevant and atypical, can acquire a criminal sense and therefore, be criminally relevant if certain conditions are met among which the incorporation of said conduct in a criminal context is essential.